Sekolah Berbasis Salafi - Syamsuriana Basri; Andi Aderus; Muhammad Amri (Peneliti.net, 2023)
This study aims to describe an overview of religious understanding among salafi circles and the problems (pros and cons) of the salafi movement in Indonesia and the development of salafi manhaj schools. This study used a qualitative-descriptive research method with library research techniques. The results of the study show that salafists follow and adhere to the Qur'ân and Sunnah, leave bid'ah, monotheism, demand useful knowledge, at-Tashfiyah and at-tarbiyah, refuse party and stagnation in schools of thought and revive true Islamic thought. based on the Qur'an, sunnah and the actions of as-salaf ash-shâlih. Salafi preachers always call for obedience to the government, among the principles of Ahlus Sunnah wal Jama'ah is the obligation to obey Muslim leaders as long as they do not order them to commit disobedience, even though they commit wrongdoing. Because obeying them is included in obedience to Allah, and obedience to Allah Subhanahu wa Ta'ala is mandatory. The solution for the actions of the movement of individuals who label themselves as salafi has caused uproar, including the government to communicate in order to minimize friction, foster a feeling of mutual respect and respect for existing differences, tools and legal certainty, and encourage the public to report the perpetrators of actions that are troubling the public to the party. authorities, the government is also expected to be a neutral judge by enforcing applicable rules and taking firm action against those who are proven to have created truth and chaos in society, religious leaders and community leaders are expected to be pro-active in dealing with various groups deemed being a trigger for problems in religious communities, being a good mediator and listener when conflicts occur between religious groups, instead of being provoked and taking sides with one of the groups and religious leaders akwah and include information on lessons at school. Then the salafi school is an effort to